«THE WEEKEND WILL LAST FOREVER»: THE CONCEPT OF THE TIME IN THE MEDIAADVERTISING IMAGE OF WORLD - Elena Nikolaevna Yezhova (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to the formation of mechanism of modern media-advertising image of world; it’s spatial and temporal organization; the concept of the time in advertising was analyzed in this article.